2013 IEEE International Test Conference (ITC) 2013
DOI: 10.1109/test.2013.6651885
|View full text |Cite
|
Sign up to set email alerts
|

True non-intrusive sensors for RF built-in test

Abstract: In this summary paper, we discuss two types of sensors that provide a buHt-in test solution for RF circuits. The key characteristic of the sensors is that they are non-intrusive, in the sense that they are not electrically connected to the RF circuit under test. This has the important advantage that the design of the RF circuit becomes totally independent from the design of the sensors. In other words, the RF circuit design methodology and performance trade-offs are totally transparent to the insertion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The efficiency of the indirect test strategy for production testing has been widely studied in the literature, including various aspects such as the choice of the regression model type, the selection of relevant indirect measurements, the use of embedded sensors, the adoption of an adaptive test flow... A comprehensive review of these works can be found in [5]. Some studies have also investigated the use of the indirect test strategy to implement Built-In Self-Test (BIST) [6,7] or to perform postmanufacturing calibration [8.9] of analog/RF circuits. However, to the best of our knowledge, the use of the indirect test strategy has never been investigated to implement on-line RF performance monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the indirect test strategy for production testing has been widely studied in the literature, including various aspects such as the choice of the regression model type, the selection of relevant indirect measurements, the use of embedded sensors, the adoption of an adaptive test flow... A comprehensive review of these works can be found in [5]. Some studies have also investigated the use of the indirect test strategy to implement Built-In Self-Test (BIST) [6,7] or to perform postmanufacturing calibration [8.9] of analog/RF circuits. However, to the best of our knowledge, the use of the indirect test strategy has never been investigated to implement on-line RF performance monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…This source can be used to measure the absolute power output of an RF circuit provided that is a tuned circuit. In [23], the authors propose to use thermal detectors that require no contact, and hence introduce no performance overhead, to correlate the thermal measurements with the gain of the DUT. This technique works very well when the DUT output is high enough to generate a thermal gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Abdallah presents a non intrusive sensor for extracting DC signatures from RF circuits in [19]. The used test vehicle is a low noise amplifier (LNA) whose functional specifications are modeled using a MARS regressor based on the aforementioned low cost DC measurements.…”
Section: Non Linear Regression: Mars Regressionmentioning
confidence: 99%
“…19 describes the algorithm which allows the densification of the test decision boundary based on an initial data set of N 0 Monte Carlo simulations. Then, the circuits are simulated and their functional specifications are obtained identifying the circuits lying near the boundary and used as a reference for selecting N extra circuits from a new and much larger N 1 samples data set.…”
mentioning
confidence: 99%